The effect of reproductive health counseling on readiness of managing menarche - Asni Asni; Luluk Husnul Dwihestie (Universitas Aisyiyah Yogyakarta, 2018)
The lack of knowledge of reproduction health contributed to the readiness toward coping menarche. It is believed that reproductive health counselling could improve the adolescents’ readiness of coping menarche. This study aimed to determine the effect of the reproductive health counseling on the adolescents’ readiness in coping menarche. This study used a quasi experimental method with non-equivalent control group. Sample of the study was 34 in the control group, and 34 in the experiment group recruited by using convenience sampling. Independent sample t-test showed that there was an effect of reproduction health counseling on the readiness in coping menarche among female students of Junior High School (p-value 0.01).